The relationship between technostress creators towards job satisfaction at Sarawak Federal Secretary office and public work department./Nurul Haliamh Ali - Ali, Nurul Haliamh (2018)
Technology is the most important part of the 21st– century workplace that any organization without some levels of technical savvy will likely failed. At its most basic level, technology helps employees to be more efficient and productive. Apart from helping employees in their daily work, it can also cause technostress as it starts to interfere with their health and happiness. Hence it can reduce their job satisfaction. How technostress happens and how far it can effect job satisfaction? To answer the question, this correlational study was carried out to identify the relationship between technostress creators and job satisfaction. This study focused on five factors that can influence job satisfaction. These five factors; techno overload, techno invasion, techno uncertainty, techno insecurity and techno complexity was adapted from Stacy L. Boyer-Davis (2014) research framework. In addition, these five factors were used to indentify which technostress creators influence the employee’s job satisfaction and which one have the strong relationship with job satisfaction. The results from the analysis were interpreted using Statistical Package for Social Sciences Software (SPSS) version 2.0. This study investigated technostress which may result from the use of technology even after work and during holiday and also the burden of work, the changing of technology that never stop, the insecurity that employee faced due to this technology and the complexity of this technology that is hard for employee to understand and learn, its influence on job satisfaction and work-life conflict.